Место коммуникаций в теории экономической безопасности - Романчик, Татьяна Владимировна (Yunona Publishing, USA, 2019)
В статье рассмотрено влияние коммуникаций на состояние экономической безопасности предприятия. Дается анализ основных факторов, влияющих на устойчивость позиций предприятия в процессе его взаимодействия с другими участниками рынка.

The article discusses the impact of communications on the state of economic security of an enterprise. The analysis of the main factors affecting the stability of the company's position in the process of its interaction with other market participants is given.
The place of communications in the theory of economic security
Keywords: предприятие; экономическая безопасность; коммуникация; информация; взаимодействие; enterprise; economic security; communication; information; interaction